Bequests, taxation and the distribution of wealth in a general equilibrium model - Martin Sexauer; Christian Kleiber; Klaus Wälde (University of Würzburg, Department of Economics, 2005)
This paper examines the role of bequests and of taxation on bequests for the distribution of wealth. We investigate a model with overlapping generations and heterogenous households where parents derive utility directly from their bequests. Using the coefficient of variation as measure of equality, bequests per se diminish the inequality of wealth since they raise private savings and hence average wealth holdings more than the dispersion of wealth. From a policy perspective, taxing bequests and redistributing government revenue lump-sum among the young generation further decreases wealth inequality. These results also hold when measuring inequality by the Gini coefficient.
Keywords: D31; H23; 330; bequest; taxation; wealth inequality; OLG model; analytical solution